Medicalizing Developments in Counsellor Education? Counselling and Counselling Psychology Students’ Views - Strong, Tom; Vegter, Vanessa; Chondros, Konstantinos; Job, Christiane (Canadian Journal of Counselling and Psychotherapy, 2017)
Counsellors have historically endorsed pluralistic approaches to practice. However, recent medicalizing trends now often shape how they are paid, regulated, and administered. The experiences and views of graduate students in counsellor education with respect to this pluralism and medicalization have not been studied. In an effort to better understand their experiences and how they reconciled (or anticipated reconciling) medicalizing expectations (e.g., use of diagnoses and evidence-based treatments) with other aspects of their learning, we conducted a nationwide survey of Canadian graduate students and recent graduates of master’s-level counsellor education programs (N = 68). We also conducted in-depth follow-up interviews (n = 9) with self-nominating survey respondents. Our interest was with representing the tensions and complexities in our participants’ reported experiences, so we used the mapping procedures of Adele Clarke’s (2005) situational analysis. We discuss the implications we associate with these mapped tensions and complexities as they relate to curricular and other aspects of counsellor education.